Classifica??o do clima local de s?tios urbanos de Feira de Santana - Sim?es, Natanael Augusto Viana (2017)
The sustainability and the renewable energies are strongly discussed and their relevance in the global community should not be discarded, after all, natural resources are limited. The problems related to the misuse and exhaustion of these resources, besides the emission of gases, occurs mainly within the cities where the majority of the human activities are developed. For this reason, among others, the interest in monitoring climatic factors within cities is growing around the world. Our objective is to identify and classify Local Climate Zones in urban areas of Feira de Santana and propose a local scale sensing infrastructure. In order to achieve the proposed target, it was necessary to explore meteorological observation methods at urban sites; establish a raw data access service and an interface for end users; and to develop a meteorological station capable of measuring the investigated parameters representatively in the urban context. Of the existing methods for classification of urban sites, we used Local Climates Zones proposed by Stewart and Oke in a universe of thirty-five sites spread throughout the city of Feira de Santana. The procedure was carried out in three stages, where temperature and humidity data were first collected using the Arduino platform; in addition to observing and evaluating afforestation, buildings (types, height, spacing and material), types of surface, width of streets, traffic of vehicles and human activity. We adopted as parameter a radius of 500m for thermal source area. As result, we obtained the sites classification, constructed two tables and a map to expose the collected data and observations made identifying each site and its class. In order to fulfill the goal of developing a station adapted to the urban environment, we propose in this work the logical organization of a framework that defines the collection of data by automatic low-cost stations connected to the internet, and the visualization of this data by means of the 52? North SOS. For the construction of the prototype stations, we take into account the sensing of temperature and humidity only for demonstration of the framework, being possible to include more types of sensors in the future. The procedure adopted for the construction took into account the exposure criteria of the WMO temperature and humidity sensors, ensuring that the measured data are relevant to the urban climate. At the end of the application of this methodology, we reached a prototype that implements the proposed framework also using the Arduino platform. All generated source code was made available in a public repository under free software license. Analyzing the descriptions of the sites studied in this work, we noticed some characteristics that make up the city of Feira de Santana in general. As for the proportion of selected Local Climate Zones, the class that best represents Feira de Santana is the Compact low-rise (LCZ 3) evaluated in 40% of the studied sites. In addition, the spatial arrangement of the zones with this classification is very homogeneous in the sense of proximity and adjacencies. We have identified serious sanitation problems that are clearly observed in the absence of sewage and water drainage. The stations were originally developed by us following the guidelines of WMO and Oke, and we achieved a low cost construction using open hardware.